Carbon Monoxide Protects Against Hemorrhagic Shock and Resuscitation–Induced Microcirculatory Injury and Tissue Injury. Issue 2 (February 2015) - Nassour, Ibrahim; Kautza, Benjamin; Rubin, Mark; Escobar, Daniel; Luciano, Jason; Loughran, Patricia; Gomez, Hernando; Scott, Jeffrey; Gallo, David; Brumfield, John; Otterbein, Leo E.; Zuckerbraun, Brian S.
<x xml:space="preserve">Abstract</x> ABSTRACT Traumatic injury is a significant cause of morbidity and mortality worldwide. Microcirculatory activation and injury from hemorrhage contribute to organ injury. Many adaptive responses occur within the microcirculatory beds to limit injury including upregulation of heme oxygenase (HO) enzymes, the rate-limiting enzymes in the breakdown of heme to carbon monoxide (CO), iron, and biliverdin. Here we tested the hypothesis that CO abrogates trauma-induced injury and inflammation protecting the microcirculatory beds. Methods: C57Bl/6 mice underwent sham operation or hemorrhagic shock to a mean arterial pressure of 25 mmHg for 120 minutes. Mice were resuscitated with lactated Ringer's at 2× the volume of maximal shed blood. Mice were randomized to receive CO-releasing molecule or inactive CO-releasing molecule at resuscitation. A cohort of mice was pretreated with tin protoporphyrin-IX to inhibit endogenous CO generation by HOs. Primary mouse liver sinusoidal endothelial cells were cultured for in vitro experiments. Results: Carbon monoxide–releasing molecule protected against hemorrhagic shock/resuscitation organ injury and systemic inflammation and reduced hepatic sinusoidal endothelial injury. Inhibition of HO activity with tin protoporphyrin-IX exacerbated liver hepatic sinusoidal injury. Hemorrhagic shock/resuscitation in vivo or cytokine stimulation in vitro resulted in increased endothelial expression of adhesion molecules that was associated with decreased leukocyte adhesion in vivo and in vitro. Conclusions: Hemorrhagic shock/resuscitation is associated with endothelial injury. Heme oxygenase enzymes and CO are involved in part in diminishing this injury and may prove useful as a therapeutic adjunct that can be harnessed to protect against endothelial activation and damage.